Thirty-six years of the Forced Concept Inventory and the Mechanics Baseline Test: is Aristotle still playing hide and seek in our classrooms? - Pérez Millán, C. (2021)
In this work, we analyze the conceptual comprehension of Newtonian Physics topics by students of different engineering careers during the first Physics course at the Universidad Nacional del Sur, in Bahía Blanca, Argentina. The Mechanics Baseline Test introduced by Hestenes and Wells more than three decades ago, is complemented with semi-structured personal interviews. The categories identified during the interviews for the concept of force and the different study techniques employed are analyzed. Present results indicate low overall conceptual comprehension. Moreover, we find clear indications that a major fraction of the interviewed students still retain Aristotelian representations even after they have passed formal exams on the topic.